2018
DOI: 10.1039/c8ra08238c
|View full text |Cite
|
Sign up to set email alerts
|

Halogeno-substituted indazoles against copper corrosion in industrial pickling process: a combined electrochemical, morphological and theoretical approach

Abstract: The inhibitive properties of four indazole-based compounds on copper corrosion in 0.5 M H2SO4 solution were investigated using electrochemical measurements and molecular modelling methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…23,25 Furthermore, Fukui function offers a useful approach to predict electron transfer reactivity, which helps researchers to better understand the electronic properties of the functional groups and conrm the main active sites of a molecule. 22,26,27 Therefore, due to the similar structure of thiadiazole and its derivatives, this study focuses on 2,5-bis (octyldithio)-1,3,4thiadiazole (BODTA) and aims to present new insights into its electrochemical and adsorption behaviors on aluminum via experimental and theoretical methods. The morphology, elements and compounds on the aluminum surface were characterized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,25 Furthermore, Fukui function offers a useful approach to predict electron transfer reactivity, which helps researchers to better understand the electronic properties of the functional groups and conrm the main active sites of a molecule. 22,26,27 Therefore, due to the similar structure of thiadiazole and its derivatives, this study focuses on 2,5-bis (octyldithio)-1,3,4thiadiazole (BODTA) and aims to present new insights into its electrochemical and adsorption behaviors on aluminum via experimental and theoretical methods. The morphology, elements and compounds on the aluminum surface were characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the quantum chemical calculations play a vital role in optimizing the molecular structure and exploring the adsorption mechanism of the inhibitor. 22 The molecular structure of the inhibitor attaches a great importance to the determination of its adsorption mechanism on the metal surface. 23 The adsorption behavior of organic compounds on the surface mainly depend on the electron donation ability as well as its acceptance capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the corrosion rate can be adopted to characterize the corrosion speed of the specimen [32, 33]. The corrosion rate of the specimen can be calculated by the following equation [34]: truenormalv1.69998pt=1.69998ptm0-ms1t4pt …”
Section: Resultsmentioning
confidence: 99%
“…Organic compounds containing heteroatoms such as N, P, S or O have been used as excellent inhibitors due to their strong electron-donating ability [4,5,6]. Additionally, due to their high adsorption capacity, indazole derivatives have attracted the attention of several researchers [7,8]. Our previous work revealed that indazole can absorb onto copper surfaces and exhibits a favorable inhibition efficiency for copper corrosion in a 3.0 wt.% NaCl solution [7].…”
Section: Introductionmentioning
confidence: 99%